2014
DOI: 10.1371/journal.pone.0088921
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low Frequency Magnetic Field (50 Hz, 0.5 mT) Reduces Oxidative Stress in the Brain of Gerbils Submitted to Global Cerebral Ischemia

Abstract: Magnetic field as ecological factor has influence on all living beings. The aim of this study was to determine if extremely low frequency magnetic field (ELF-MF, 50 Hz, 0.5 mT) affects oxidative stress in the brain of gerbils submitted to 10-min global cerebral ischemia. After occlusion of both carotid arteries, 3-month-old gerbils were continuously exposed to ELF-MF for 7 days. Nitric oxide and superoxide anion production, superoxide dismutase activity and index of lipid peroxidation were examined in the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 64 publications
8
29
0
2
Order By: Relevance
“…There are limited data supporting the antioxidant effect of ELF‐EMF, in particular its positive impact on improving the functioning connective tissue's cells [Sosnowski et al, ; Kurzeja et al, ]. We have observed an increase of SOD activity in the hemolysate, with results that are consistent with data presented by Rauš Balind et al []. Those authors demonstrated that ELF‐EMF decreased the level of oxidative stress in gerbil brains with induced global cerebral ischaemia, as demonstrated by amplified SOD activity [Rauš Balind et al, ].…”
Section: Discussionsupporting
confidence: 89%
“…There are limited data supporting the antioxidant effect of ELF‐EMF, in particular its positive impact on improving the functioning connective tissue's cells [Sosnowski et al, ; Kurzeja et al, ]. We have observed an increase of SOD activity in the hemolysate, with results that are consistent with data presented by Rauš Balind et al []. Those authors demonstrated that ELF‐EMF decreased the level of oxidative stress in gerbil brains with induced global cerebral ischaemia, as demonstrated by amplified SOD activity [Rauš Balind et al, ].…”
Section: Discussionsupporting
confidence: 89%
“…Alterations in inflammatory responses have also been observed, but how these activities affect human health remains unknown [23].…”
Section: Introductionmentioning
confidence: 99%
“…PEMF is an FDA-approved therapy presenting benefices for the treatment of several musculoskeletal disorders, however there is controversy about the role of magnetic fields in oxidative stress. Some studies suggested that magnetic fields, accounting their strength and amplitude are endowed with the ability to generate potentially harmful ROS [29], while others demonstrated that magnetic fields selectively decreased the viability of malignant cells [30], reduced oxidative stress in the brain of Gerbils [31] and activated endogenous clearance mechanisms to remove ROS [16]. We found no differences in ROS production between static and magnetic conditions suggesting that environmental stress produced by magnetically actuated biomaterials is not perceived by hASCs as harmful.…”
Section: Discussionmentioning
confidence: 49%